Techno-economic analysis of on-grid biomass renewable energy power station: A case study in Caribbean region of Colombia (2018)
In this article a techno-economic study of an Electric-Biomass on-grid power plant is presented, in order to compare the performance and the operating annual cost under some types of biogas produced from poultry, bovine and porcine manure, and solid urban organic waste, using the Homer® software to develop many solutions. Certainly, the best set up had the maximum combined renewable energy with a minimum electric consumption from the grid. The scheme was integrated by two 500kW biogas-powered electric generator on grid to supply an average energy of 1401.6kW, with an annual operating cost of $2.09 million when the energy supply is electric. Results presented a significant operational cost reduction when the biogas generator is operating on grid, finding an 8.61% of cost decrease using biogas generated from poultry, bovine and porcine manure, and a 10.53% of cost decrease using biogas from solid urban organic waste from centers and grocery market places at Caribbean Region of Colombia.